2021
DOI: 10.1007/s12055-021-01217-x
|View full text |Cite
|
Sign up to set email alerts
|

Practical considerations for developing a lung transplantation anesthesiology program

Abstract: The advancement in lung transplantation outcomes has been secondary to ongoing improvements within multiple medical specialties. The recent emergence of literature describing the impact of anesthetic management on perioperative outcomes has led to the beginnings of formalized training fellowships within lung transplantation anesthesiology. Practical considerations for the development of a lung transplantation anesthesiology program, both clinical and educational, are herein described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…After the ECMO is weaned, TEE evaluation to assess the patency and peak velocities of pulmonary vasculature anastomoses should be performed utilizing color flow, continuous wave, and pulsed wave Dopplers. 29…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the ECMO is weaned, TEE evaluation to assess the patency and peak velocities of pulmonary vasculature anastomoses should be performed utilizing color flow, continuous wave, and pulsed wave Dopplers. 29…”
Section: Discussionmentioning
confidence: 99%
“…After the ECMO is weaned, TEE evaluation to assess the patency and peak velocities of pulmonary vasculature anastomoses should be performed utilizing color flow, continuous wave, and pulsed wave Dopplers. 29 Postoperative continuation of ECMO is utilized in the setting of PGD or if the ESLD is primary pulmonary hypertension. 19 In the setting of PGD, early initiation of VV ECMO is linked to improved survival outcomes, whereas prolongation of VA ECMO in patients with primary pulmonary hypertension allows for gradual biventricular remodeling.…”
Section: Intraoperative Ecmo and Ventilation Managementmentioning
confidence: 99%
“…If cannulation is necessary, TEE is vital in guiding aortic and venous cannulation ( 87 ). Intracardiac shunts should be identified as shifts in right atrial (RA) and left atrial (LA) pressure can cause shunt reversal and hypoxia ( 80 , 84 , 88 ). Of note, Subramaniam found that 12.7% respondents in their survey always closed a patent foramen ovale (PFO), while 24.9% did not and the majority intervened on a case-by-case basis ( 89 ).…”
Section: Perioperative Echocardiographymentioning
confidence: 99%
“…The role of a perioperative TEE service is vital in the care of LTx recipients. TEE is a quick and feasible bedside exam that provides immediate diagnostic information allowing for guided therapeutic intervention ( 88 ). Although anesthesiologists are already using TEE for most LTxs, further evidence is needed from large, multicenter studies to better establish quantifiable echocardiographic parameters for normal and abnormal findings.…”
Section: Perioperative Echocardiographymentioning
confidence: 99%
“…1,2 A key intersection of multidisciplinary teams (MDTs) and COVID-19 is found in lung transplantation, in which diverse teams collaborate throughout the perioperative period to achieve optimal outcomes in patients with ESLD. 3,4 The first major case series describing early outcomes in lung transplantation focused on the surgical considerations for COVID-19 as well as preliminary proposed criteria for pursuing transplantation in patients with COVID-19erelated ESLD. 5 Since then, several other high-volume centers have published their institutional experience in lung transplantation for COVID-19.…”
mentioning
confidence: 99%